Fetal indusium griseum is a possible biomarker of the regularity of brain midline development in 3T MR imaging: A retrospective observational study - Ivana Pogledic; Mihaela Bobić‐Rasonja; Christian Mitter; Andrija Štajduhar; Ernst Schwartz; Marija Milković‐Periša; Pascal A. Baltzer; Maarten Lequin; Elisabeth Krampl‐Bettelheim; Gregor Kasprian; Miloš Judaš; Daniela Prayer; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction This study aimed to assess the visibility of the indusium griseum (IG) in magnetic resonance (MR) scans of the human fetal brain and to evaluate its reliability as an imaging biomarker of the normality of brain midline development. Material and methods The retrospective observational study encompassed T2‐w 3T MR images from 90 post‐mortem fetal brains and immunohistochemical sections from 41 fetal brains (16–40 gestational weeks) without cerebral pathology. Three raters independently inspected and evaluated the visibility of IG in post‐mortem and in vivo MR scans. Weighted kappa statistics and regression analysis were used to determine inter‐ and intra‐rater agreement and the type and strength of the association of IG visibility with gestational age. Results The visibility of the IG was the highest between the 25 and 30 gestational week period, with a very good inter‐rater variability (kappa 0.623–0.709) and excellent intra‐rater variability (kappa 0.81–0.93). The immunochemical analysis of the histoarchitecture of IG discloses the expression of highly hydrated extracellular molecules in IG as the substrate of higher signal intensity and best visibility of IG during the mid‐fetal period. Conclusions The knowledge of developmental brain histology and fetal age allows us to predict the IG‐visibility in magnetic resonance imaging (MRI) and use it as a biomarker to evaluate the morphogenesis of the brain midline. As a biomarker, IG is significant for post‐mortem pathological examination by MRI. Therefore, in the clinical in vivo imaging examination, IG should be anticipated when an assessment of the brain midline structures is needed in mid‐gestation, including corpus callosum thickness measurements.